Association Between Birth Weight, Birth Length, and Stunting: A Case Analysis at Lempake Public Health Center, East Kalimantan, Indonesia - Rahayu, Hanis Kusumawati; Muhlis, Abdu Nafan Aisul; Bakhtiar, Rahmat; Wijaya, Ramadhani Hengki; Akbar, M. Fachrian; Dzakwan, Sya'idah Alawiah; Rozi, Imam Fathur; Rusdi, Alief Fikri (Universitas Airlangga, 2025)
Stunting remains a significant public health concern in Indonesia, as it affects early childhood growth and development, leading to long-term health and cognitive impairments. Birth length and birth weight are critical predictors of stunting, as inadequate growth parameters at birth may contribute to poor nutritional status and delayed development. Toddlers, particularly those in low-resource settings, are among the most vulnerable age groups to dietary deficiencies, making early identification of risk factors essential for prevention efforts. This study aimed to assess the association between birth weight, birth length, and the incidence of stunting among children at Lempake Community Health Center in Samarinda, Indonesia. A quantitative analytic observational study with a case-control design was conducted to evaluate the relationship between these perinatal factors and stunting risk. The findings revealed that stunting was more prevalent among male infants (51.1%) aged 0–11 months. A statistically significant association was observed between birth weight and stunting (p = 0.00), with an odds ratio of 0.414 (95% CI: 0.23–0.72), indicating that children born with a birth weight of <2500 grams had a higher likelihood of experiencing stunting. Similarly, birth length was significantly associated with stunting (p =0.02), with an odds ratio of 0.264 (95% CI: 0.13–0.50), suggesting that infants with a birth length of <48 cm were at an increased risk. These findings underscore the importance of monitoring birth weight and length as early indicators for stunting prevention strategies in Indonesia.